Pengaruh Nilai, Rating, Umur Penerbitan Obligasi Syariah (Sukuk) Perusahaan Terhadap Return Saham Pada Perusahaan-Perusahaan Yang Menerbitkan Obligasi Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Silvia Firmayeska (CV. ITTC INDONESIA, 2023)
This study aims to determine the influence of value, rating, age of issuance of Islamic bonds (Sukuk) of companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample selection technique uses a purposive sampling method so that a sample of 14 companies is obtained with 28 observational data. The test was carried out with the help of SPSS 24 (Statistical Product and Service Solution) and data analysis was used in this study using multiple linear regression analysis. The results showed that the sukuk value variable had a positive and significant effect on stock returns, while the sukuk rating variable had no effect on stock returns, and the sukuk age variable had no effect on stock returns.